Ecocritical of Climate Crisis: Drought 2023 Documentary Film: The Relationship between Human and Environment - Fathinah, A. Nur Fikriyyah; Asyrafunnisa, Asyrafunnisa; Rosmawati, Rosmawati (Fakultas Sastra, Universitas Bosowa, 2024)
This study explored the ecocritical dimensions in the documentary film Climate Crisis: Drought 2023, focussing on the complex relationship between humans and the environment, types of ecocriticism, and the documentary’s message through an ecocritical lens. This study used a qualitative descriptive methodology to analyse the narrative in the documentary film Climate Crisis: Drought 2023, utilising Greg Garrard’s ecocritical theory. The research findings showed the relationship between humans and nature in the representation of various ecocritical themes, including pollution, wilderness, apocalypse, shelter, animals, and the earth. Also, it identified the types of ecocriticism presented in the film, including postcolonial ecocriticism, wilderness ecocriticism, ecofeminism, material ecocriticism, and postmodern ecocriticism. These findings, highlighted the extent to which human activities and climate change affect natural ecosystems and the urgency of sustainable action, which is the message in this film documentary. It was concluded that the documentary did an excellent job of conveying important ecological challenges of the moment and encouraging audiences to consider their own involvement in protecting the environment. By highlighting the significance of incorporating ecological perspectives in literary and media analysis, this study offered insightful information for further environmental research.